Comparing preservice teachers' professional noticing skills in elementary mathematics classrooms. (14th February 2019) - Fisher, Molly H.; Thomas, Jonathan; Jong, Cindy; Schack, Edna O.; Dueber, David
Abstract: This paper examines the implementation of an instructional module on preservice elementary teachers' professional noticing of children's mathematical thinking. The module focuses on professional noticing skills through the content focus of early algebraic reasoning and uses complex video vignettes from whole class instruction in authentic elementary mathematics classrooms. Findings indicated that two of the three components of professional noticing (attending and interpreting) showed statistically significant increases in a treatment group that did not occur in a comparison group. The deciding component remains a challenge that warrants further research.